The Relationship of Mother's Knowledge Level And Mp-Asi Feeding Patterns and Baby's Nutritional Status Age 6-12 Months at Rantang Health Center - Lubis, Basyariah; Tioman Deliana (JURNAL KEBIDANAN KESTRA (JKK), 2024)
The toddler period is a very important period and needs serious attention. During this period the life process of growth and development takes place very rapidly, namely physical growth and psychomotor, mental and social development. The nutritional status of children under five is an important thing that must be known by every parent. Mothers play an important role in supporting efforts to overcome nutritional problems, especially in terms of family nutrition, starting from food preparation, selection of food ingredients, to the food menu. Mothers who have good nutritional status will give birth to well-nourished children. Lack of parental nutrition and health knowledge, especially mothers is one of the causes of malnutrition in children under five. Mother's knowledge about nutrition is what the mother knows about healthy food for a certain age group and how the mother chooses, processes and prepares food properly. The aim is to determine the relationship between the mother's level of knowledge and the pattern of complementary feeding of breast milk on the nutritional status of toddlers 6-12 months in the working area of the Rantang Health Center, Sei Putih Tengah Village, Medan Petisah District, North Sumatra. This type of research is an analytic method with a cross sectional approach. The sample in this study were all children aged 6-12 months inti the Rantang Health Center, namely 54 children. Bivariate analysis used the Chi-Square (?2) statistical test. The results of the statistical test obtained a p value of 0.002 (? <0.05), which means that there is a relationship, namely the relationship between maternal nutritional knowledge regarding the pattern of giving complementary foods and the nutritional status of toddlers aged 6-24 months